2020
DOI: 10.1002/pssb.201900598
|View full text |Cite
|
Sign up to set email alerts
|

Interface Studies in HgTe/HgCdTe Quantum Wells

Abstract: Transmission electron microscopy (TEM) is used for the study of interfaces in two HgTe/HgCdTe single quantum‐well (QW) structures grown by molecular beam epitaxy on GaAs substrates. The studies are conducted in bright‐field and scanning/high‐angle annular dark field modes. The effect of the growth mode on the sharpness of interfaces in the QWs is investigated. Effective in situ ellipsometric control over chemical composition and thickness of the layers constituting the QW structures is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…High-resolution images of “dark areas” from the overview micrographs ( Figure 1 b) revealed defects similar to the ones studied in a recent work [ 38 ].Based upon the lateral average of contrast, we obtain the average width for QWs d = 8–12 nm. Notably, the QW width determined from TEM images in a recent work was also 2 nm larger than that extracted from the ellipsometry data [ 20 ]. One can anticipate that Cd is present in QW because pure HgTe QW would have an inverted band structure, resulting in a bandgap of 20 meV at the most, which is in poor agreement with the observed PC cutoff and SE wavelength (see below).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…High-resolution images of “dark areas” from the overview micrographs ( Figure 1 b) revealed defects similar to the ones studied in a recent work [ 38 ].Based upon the lateral average of contrast, we obtain the average width for QWs d = 8–12 nm. Notably, the QW width determined from TEM images in a recent work was also 2 nm larger than that extracted from the ellipsometry data [ 20 ]. One can anticipate that Cd is present in QW because pure HgTe QW would have an inverted band structure, resulting in a bandgap of 20 meV at the most, which is in poor agreement with the observed PC cutoff and SE wavelength (see below).…”
Section: Resultsmentioning
confidence: 98%
“…Commonly used characterization techniques are often challenging for HgCdTe. In particular, there are not many papers on transmission electron microscopy of HgCdTe heterostructures [ 19 , 20 ], and the photoluminescence (PL) studies of HgCdTe in the very long wavelength range are also quite scarce [ 21 , 22 ]. Complications in PL studies are related to low efficiency of light emission and less sensitive detectors in the long wavelength region.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the high-energy PL lines in the samples under study were due to optical transitions caused by the recombination of excitons localized on composition fluctuations [12] and, accordingly, showed a significant disordering of the solid solution. The last statement, as shown by X-ray diffraction and microscopic studies of such material [7,8,13,14], cannot always be directly related to its structural quality. The potential influence of this disordering on the energy spectrum of carriers in LS should be the subject of additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Together with the growth temperature, absolute film thickness, and growth rate determined by SE in real time, they investigated the temperature dependence of the dielectric function of Bi 2 Se 3 , showcasing the exceptional capability and potential of SE in optimizing film quality and improving reproducibility [19] . SE can also facilitate the measurement of the composition distribution over epitaxial film thickness [141,142] . Shvets et al adopted SE to study cadmium-mercury-tellurium compounds' thickness dependence of the composition, highlighting its potential in accurate reproduction of the composition profile for the heterostructures [143] .…”
Section: Spectroscopic Ellipsometry (Se)mentioning
confidence: 99%